Fe(OH)3 + 3HNO3 = больше Fe(NO3)3 +3H2O K2CO3 + H2SO4 = K2SO4 + CO2↑ + H2O NaOH+Al(OH)3= NaAlO2 + 2H2O полное йонное и скороченне йонне уравнения
Fe(OH)3 + 3HNO3 => Fe(NO3)3 +3H2O K2CO3 + H2SO4 = K2SO4 + CO2↑ + H2O NaOH+Al(OH)3= NaAlO2 + 2H2O полное йонное и скороченне йонне уравнения
Ответ(ы) на вопрос:
Fe(OH)3 + 3HNO3 => Fe(NO3)3 +3H2O Fe (3+) + 3OH (1-) + 3H (1+) + 3NO3 (1-) = Fe (3+) + 3NO3 (1-) + 3H2O 3OH (1-) + 3H (1+) = 3H2O K2CO3 + H2SO4 = K2SO4 + CO2↑ + H2O 2K (1+) + CO3 (2-) + 2H (1+) + SO4 (2-) = 2K (1+) + SO4 (2-) + CO2 + H2O 2H (1+) + CO3 (2-) = CO2 + H2O NaOH+Al(OH)3= NaAlO2 + 2H2O Na (1+) + OH (1-) + Al (3+) + 3OH (1-) = Na (1+) + Al (3+) + O2 (2-) + 2H2O OH (1-) + 3OH (1-) = 2H2O
Не нашли ответ?
Похожие вопросы